A Genome‐Wide Assessment of Variability in Human Serum Metabolism. Issue 3 (18th February 2013) - Hong, Mun‐Gwan; Karlsson, Robert; Magnusson, Patrik K. E.; Lewis, Matthew R.; Isaacs, William; Zheng, Lilly S.; Xu, Jianfeng; Grönberg, Henrik; Ingelsson, Erik; Pawitan, Yudi; Broeckling, Corey; Prenni, Jessica E.; et al.
<x xml:space="preserve">Abstract</x> A genome‐wide association study of metabolic quantitative traits (mQTLs) was conducted in Swedish men. A global non‐targeted metabolite profiling approach was used resulting in the identification of both novel mQTLs and replication of previously described associations. Analyses involving biological pathways and a search for enrichment of mQTLs across the genome highlighted additional novel loci. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>